2013
DOI: 10.1021/pr400869u
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Conformation and Binding Interface of Cap-Binding Proteins and Complexes via Ultraviolet Photodissociation Mass Spectrometry

Abstract: We report the structural analysis of cap-binding proteins using a chemical probe/ultraviolet photodissociation (UVPD) mass spectrometry strategy for evaluating solvent accessibility of proteins. Our methodology utilized a chromogenic probe (NN) to probe the exposed amine residues of wheat eukaryotic translation initiation factor 4E (eIF4E), eIF4E in complex with a fragment of eIF4G ("mini-eIF4F"), eIF4E in complex with full length eIF4G, and the plant specific cap-binding protein, eIFiso4E. Structural changes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 10 publications
(31 citation statements)
references
References 81 publications
0
31
0
Order By: Relevance
“…A constitutively reduced mutant (C113S) and oxidized forms of eIF4E bound m 7 GTP with a modest 1.5x difference in k off values in NMR (nuclear magnetic resonance) solution studies (Monzingo et al, 2007). Further studies using mass spectrometry and a lysine-specific chemical probe indicated structural changes occurred upon altering the redox state and support the hypothesis of a redox sensor or switch for eIF4E (O'Brien et al, 2013). It remains a tantalizing possibility that the oxidation state of eIF4E (and/or eIFiso4E) may modulate cap binding in a redox-sensing manner in plants during retrograde signaling from the chloroplast to nucleus or other processes that could regulate the level of translation in response to the redox state of the cell.…”
Section: The Cast Of Cap-binding Proteins: Eif4e Eifiso4e and 4ehpmentioning
confidence: 80%
“…A constitutively reduced mutant (C113S) and oxidized forms of eIF4E bound m 7 GTP with a modest 1.5x difference in k off values in NMR (nuclear magnetic resonance) solution studies (Monzingo et al, 2007). Further studies using mass spectrometry and a lysine-specific chemical probe indicated structural changes occurred upon altering the redox state and support the hypothesis of a redox sensor or switch for eIF4E (O'Brien et al, 2013). It remains a tantalizing possibility that the oxidation state of eIF4E (and/or eIFiso4E) may modulate cap binding in a redox-sensing manner in plants during retrograde signaling from the chloroplast to nucleus or other processes that could regulate the level of translation in response to the redox state of the cell.…”
Section: The Cast Of Cap-binding Proteins: Eif4e Eifiso4e and 4ehpmentioning
confidence: 80%
“…There is also experimental evidence that the looped region around the Lys165 and Arg166 residues interacts with the mRNA cap. 53 UVPD of the holo -eIF4E (Figure 2) generated a wide variety of fragment ions that retained m 7 GTP (a subset of m 7 GTP-bound fragment ions is shown in Table S2). The UVPD fragmentation map of the eIF4E/m 7 GTP complex (8+) displays the backbone cleavage sites that lead to fragment ions that retain m 7 GTP (red cleavage marks in Figure 2C).…”
Section: Resultsmentioning
confidence: 99%
“…Despite that the two cysteines involved are strictly conserved in plant eIF4Es, suggesting that they may have some important biological role, affinity-binding assays under both reducing and oxidizing conditions showed that in both cases wheat eIF4E retained the ability to bind the cap (Monzingo et al, 2007). However, further studies using mass spectrometry and a Lys-specific chemical probe indicated structural changes upon altering the redox state, supporting the hypothesis of a redox sensor or switch for eIF4E (O'Brien et al, 2013). Whether the oxidation state of eIF4E may modulate cap binding in a redox-sensing manner in plants and regulate the level of translation in response to the redox state of the cell remains uncertain.…”
Section: Peculiarities Of the Plant Eif4e-eif4g 1003-1092 Complexmentioning
confidence: 91%